2023
DOI: 10.3390/microorganisms11020298
|View full text |Cite
|
Sign up to set email alerts
|

The Vaginal Microbiome in Health and Disease—What Role Do Common Intimate Hygiene Practices Play?

Abstract: The vaginal microbiome is a dynamic, sensitive microenvironment. The hallmark of a ‘healthy’ vaginal microbiome is currently believed to be one dominated by Lactobacillus spp., which acidifies the vaginal environment and help to protect against invading pathogens. However, a ‘normal’ microbiome is often difficult, if not impossible, to characterise given that it varies in response to numerous variables, including pregnancy, the menstrual cycle, contraceptive use, diet, ethnicity, and stress. A Lactobacillus-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
6

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 146 publications
0
25
0
6
Order By: Relevance
“…The high incidence of PID among the participants (73%) is noteworthy, as it suggests a potential association between vaginal douching and the development of PID. Vaginal douching involves the rinsing or cleaning of the vaginal area with various substances, which may disrupt the natural balance of bacteria and increase the risk of infections such as PID 19,35 . The findings underscore the importance of caution and informed decision‐making when considering vaginal douching practices.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The high incidence of PID among the participants (73%) is noteworthy, as it suggests a potential association between vaginal douching and the development of PID. Vaginal douching involves the rinsing or cleaning of the vaginal area with various substances, which may disrupt the natural balance of bacteria and increase the risk of infections such as PID 19,35 . The findings underscore the importance of caution and informed decision‐making when considering vaginal douching practices.…”
Section: Discussionmentioning
confidence: 94%
“…Vaginal douching involves the rinsing or cleaning of the vaginal area with various substances, which may disrupt the natural balance of bacteria and increase the risk of infections such as PID. 19,35 The findings underscore the importance of caution and informed decisionmaking when considering vaginal douching practices.…”
Section: Knowledge and Perception Of Vaginal Douchingmentioning
confidence: 85%
See 1 more Smart Citation
“…In a previous study, approximately 40% of women with UTI self-reported that they had UTI signs after menstruation [ 4 ]. Contaminated vaginal discharges and/or the changed vaginal microbiome during the menstruation period may underlie these findings [ 14 , 15 ]. If these theories are correct, the post-toilet habit of wiping the bottom from behind is better to be performed both for vaginal hygiene practice during the menstruation period and anal hygiene practice after defecation to prevent UTI events.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller proportion of females have a vaginal microbiota that is not dominated by lactobacilli, but is instead composed of a balanced population of obligate and facultative anaerobes, mostly characterized by genera Gardnerella , Atopobium and Prevotella . Due to the low presence of lactobacilli, this type of vaginal microbiota profile is associated with a higher risk of infections and adverse health outcomes [ 17 , 18 , 19 ]. The observed protective function of the vaginal microbiota characterized by low diversity and domination by Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%